Teaching English Based on The Kurikulum Merdeka at Muhammadiyah Junior High Schools in Yogyakarta: The Teachers’ Implementation and Perception - Heri Riskianto; Surono Surono; Iin Inawati (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This research aims to reveal the implementation and perceptions of the Kurikulum Merdeka by English teachers and also to find the English teachers’ problems in implementing the Kurikulum Merdeka. This research belonged to a qualitative study conducted by using interview and observation to collect data. The research participants were three English teachers at three Muhammadiyah Junior High Schools in Yogyakarta who had implemented the Kurikulum Merdeka. Interview guidelines, observation checklist, and observation field note were used as research instruments. This research used coding technique to analyze data. The research findings showed that the English teachers implemented the Kurikulum Merdeka by varying the learning process, adapting to the students’ characters, requiring more preparations, focusing the learning on vocabulary mastery, reading literacy, and the use of technology. In other words, the Kurikulum Merdeka has not been successfully implemented. Then, the teachers’ perceptions on the Kurikulum Merdeka were actually good but still confusing; the learning resources of Kurikulum Merdeka for teachers were diverse; the Kurikulum Merdeka demanded the development of better education and more differentiated learning; and the schools needed to change the learning activity budget and did a longer assessment analysis. Lastly, the problems in the Kurikulum Merdeka faced by English teachers were the lack of teachers’ understanding on the diverse students’ characters, the lack of equipment that supported learning English in the Kurikulum Merdeka, the need for a change in the mindset of parents about implementing the Kurikulum Merdeka, and the lack of understanding of the Kurikulum Merdeka.